Visualizing Winchester: a brand history through iconic Western images. (19th November 2018) - Witkowski, Terrence H.
Abstract : Purpose: This paper aims to present a visually documented brand history of Winchester Repeating Arms through a cultural analysis of iconic Western images featuring its lever action rifles. Design/methodology/approach: The study applies visual culture perspectives and methods to the research and writing of brand history. Iconic Western images featuring Winchester rifles have been selected, examined, and used as points of departure for gathering and interpreting additional data about the brand. The primary sources consist chiefly of photographs from the nineteenth century and films and television shows from the twentieth century. Most visual source materials were obtained from the US Library of Congress, the Smithsonian Institution, the Buffalo Bill Center of the West and the Internet Movie Firearms Database. These have been augmented by written sources. Findings: Within a few years of the launch of the Winchester brand in 1866, visual images outside company control associated its repeating rifles with the settlement of the American West and with the colorful people involved. Some of these images were reproduced in books and others sold to consumers in the form of cartes de visite, cabinet cards and stereographs made from albumen prints. Starting in the 1880s, the live Wild West shows of William F. Cody and his stars entertained audiences with a heroic narrative of the period that included numerous Winchesters. During the twentieth century and into the present, Winchesters have been featured in motion pictures and television series with Western themes. Research limitations/implications: Historical research is an ongoing process. The discovery of new primary data, both written and visual, may lead to a revised interpretation of the selected images. Originality/value: Based largely on images as primary data sources, this study approaches brand history from the perspective of visual culture theory and data. The research shows how brands acquire meaning not just from the companies that own them but also from consumers, the media and other producers of popular culture.